2018
DOI: 10.1177/0748233717748099
|View full text |Cite
|
Sign up to set email alerts
|

Short-term induction of vitellogenesis in the immature male yellowfin seabream (Acanthopagrus latus) exposed to bisphenol A and 17β-estradiol

Abstract: Bisphenol A (BPA) is a known environmental endocrine-disrupting chemical that is widely used in plastics manufacturing. BPA enters in the aquatic environment mainly through urban and industrial sewage effluents, thereby posing a potential threat to organisms living in these ecosystems. This study was conducted to investigate the effect of BPA on VTG production with direct (sodium dodecyl sulfate-polyarylamide gel electrophoresis) and indirect (alkali-labile phosphate (ALP), total plasma calcium and protein) me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 61 publications
0
6
0
3
Order By: Relevance
“…Sparidae is a group of teleost fish with different reproductive strategies, including gonochorism and hermaphroditism. For example, the common dentex (Dentex dentex) is a gonochoristic species (Tsakogiannis et al, 2018a), red porgy (Pagrus pagrus), and common pandora (pagellus erythrinus) are protogynous hermaphrodites (Tsakogiannis et al, 2018b), gilthead seabream (Sparus aurata), and yellowfin seabream (Acanthopagrus latus) are protandrous hermaphrodites (Negintaji et al, 2018;Tsakogiannis et al, 2018a), and sharpsnout seabream (Diplodus puntazzo) is a rudimentary hermaphrodite fish species (Papadaki et al, 2018). Therefore, Sparidae is a good model for studying SD and sex reversal.…”
Section: Introductionmentioning
confidence: 99%
“…Sparidae is a group of teleost fish with different reproductive strategies, including gonochorism and hermaphroditism. For example, the common dentex (Dentex dentex) is a gonochoristic species (Tsakogiannis et al, 2018a), red porgy (Pagrus pagrus), and common pandora (pagellus erythrinus) are protogynous hermaphrodites (Tsakogiannis et al, 2018b), gilthead seabream (Sparus aurata), and yellowfin seabream (Acanthopagrus latus) are protandrous hermaphrodites (Negintaji et al, 2018;Tsakogiannis et al, 2018a), and sharpsnout seabream (Diplodus puntazzo) is a rudimentary hermaphrodite fish species (Papadaki et al, 2018). Therefore, Sparidae is a good model for studying SD and sex reversal.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental degradation by anthropic activities strongly affects ecosystems, mainly due to exposure to various contaminants (Solaun et al 2021). Even when present in concentrations in the order of μg L -1 and ng L -1 , several substances can cause risks to both human and animal health (Liu et al 2018;Negintaji et al 2018). Concerns regarding the quality of water resources are extremely relevant, due to significant increases in emerging micropollutants, as well as their by-products and metabolites originating from the chemical and biological degradation of the original compounds (Locatelli et al 2016;Zhong et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The use of qPCR assay for VTG mRNA in several teleosts has been developed in other countries (Ciu et al 2017;Mushirobira et al 2020) and they are used as the basis for policy formulation and monitoring aquatic environments. In previous studies, optimization of the qPCR assay is done using sexually mature females (Bowley et al 2010) or hormonally induced males (Caspillo et al 2014;Negintaji et al 2018) to ensure the presence of VTGs and then characterize the isolated VTG, and sequenced. Some fish species used in VTG quantification studies were zebrafish, Danio rerio (Humble et al 2013;Chen et al 2018), tilapia, Oreochromis mossambicus (Celino-Brady et al 2019;Chen et al 2020), These studies showed that the presence of VTG in male fish is a good biomarker for contamination of estrogens.…”
Section: Introductionmentioning
confidence: 99%